Intelligent Command Filter Design for Strict Feedback Unmodeled Dynamic MIMO Systems With Applications to Energy Systems - Feng, Xuxiang; Shi, Lu; Zhang, Yumeng (Frontiers in Energy Research, 2022)
This paper presents a command filtered control scheme for multi-input multi-output strict feedback nonlinear unmodeled dynamical systems with its applications to power systems. To deal with the dynamic uncertainties, a dynamic signal is introduced, together with radial basis function neural networks to overcome the influences from the dynamic uncertainties. Command filters are utilized to prevent the explosion of complexity, where the compensating signals can eliminate the effect of filter errors. Compared to single-input single-output strict feedback nonlinear systems, the method proposed in this paper has more suitability. In the end, the simulation experiments are carried out by applying the developed algorithm to power systems, where the simulation results verify the efficacy of the approach proposed.